Elections related cycles in publicly supplied goods in Albania - Holger Kächelein; Endrit Lami; Drini Imami (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2010)
The phenomena of manipulation of the economy by the incumbent for electoral purpose are called Political Business Cycles (PBC), introduced by Nordhaus (1975). Using policy control economic instruments, as fiscal and monetary instruments, government may manipulate the economy to gain electoral advantage by producing growth and decreasing unemployment before elections. In addition to increased public expenditures, also the production/supply of certain publicly provided goods may score improvements. In Albania, production and supply of electricity (for the time span of our analyzes) was controlled by KESH (Korporata Energjitike Shqiptare - Albanian Energy Corporation) which is a quasi- monopoly in the supply of electricity in Albania, and it is publicly run. Throughout the transition, supply of electricity, due to various technical and economic reasons, has not been stable, and characterized by systematic interruption for households and businesses users, affecting their well-being and performance (electricity is a main source of energy for households, including heating and cooking). Therefore, it seems so that there is an incentive and rationale for the incumbent to use also the provision of electricity to impress the voters before elections, beside of the classical instruments of expenditures. In this paper we analyze consumption, production and import of electricity in Albania. Our hypothesis is that before elections, electricity consumption may increase above usual levels, followed by a contraction after elections. In our analysis we use modern standard econometric approach, used widely for research related to PBC. By ARMA modelling it is possible to prove if elections can explain changes in electricity production, in addition to the past history of the variable and the random error term.
Keywords: P26; E32; D72; H72; 330; Political Business Cycle; Electricity; Albania; Elektrizitätspolitik; Elektrizitätswirtschaft; Politischer Konjunkturzyklus; Öffentliches Gut; Albanien